Building public innovation for industrial risk prevention and crisis management: Genesis and development of a unique collaborative innovation - Crivellari, Paolo (Social Science Information)
Public innovation is a peculiar form of innovation that provides new policies, new products, new services, and new infrastructures to increase public value. Many barriers can prevent this kind of innovation, so it cannot be taken for granted. Consequently, it is important to understand the conditions that can produce it. The present article is a case study on SIMAGE, a collaborative public innovation that has no equivalent in Europe and was developed in the Italian petrochemical site of Porto Marghera (in the municipality of Venice) for industrial risk prevention and crisis management. Based on sociological research conducted with qualitative techniques, I aim at accounting for the genesis and development of the process that led the public and the private sector to build jointly an effective public innovation through collaboration. The conclusion focuses on innovation processes, on the production of public goods by the public and the private sector, and on risk and crisis governance. - Reproduced.
Keywords: Collaborative innovation; Crises management; Innovation; Public innovation